Konsumsi, Tabungan, dan Investasi Dalam Syariah Makro Ekonomi - Leny Julika; Siti Aisyah Adelina; Muhammad Albahi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic economics integrates Sharia principles into economic activities, emphasizing a balance between material and spiritual needs to achieve collective welfare. This study aims to explore how national income, exports, and imports are viewed in Islamic economics, contrasting with conventional economics that prioritizes wealth accumulation and efficiency. In Islamic economics, national income considers not only material value but also equitable wealth distribution to prevent social inequality. Exports and imports are seen as instruments for both economic and social benefit, including da’wah (spiritual outreach). The results indicate that Islamic economics prioritizes justice, halal standards, and sustainability in international trade, with the government playing a crucial role in aligning policies with Sharia principles.